Use of the WinTR-55 Hydrologic Model on Determination of Flood Peak Discharge: The Case of Kirklareli Vize Stream and Samsun Minoz Stream Watersheds - Çayan Alkan (Doğal Afetler ve Çevre Dergisi)
Climate change is the main parameter affecting water resources. This parameter will exacerbate hydrologic extreme events like drought and flood. Determination of possible peak flow in the agricultural watershed is important in terms of preventing crop losses. The materials and the methods suitable for agricultural watersheds (hydrology) were used in this study. The general aim of this study is to determine the success of estimation power of the Windows Technical Release-55 (WinTR-55) Model. In this study, the peak flows estimated by the WinTR-55 model using the data of the Kirklareli Vize and Samsun Minoz Stream watersheds were compared with the observed peak flows. The most successful estimation was for the 100-year return period with error 25% in the Vize stream watershed and was for the 10-year return period with error 2% in the Minoz Stream watershed. With the aid of the WinTR-55, which tends to predict larger peak flow rates, greater peak flow rates were estimated compared with observed peak flow for each return period. So, it was understood that WinTR-55 can be used for the prevention of flood damage in the Vize and Minoz Stream watersheds confidently. As a result, it is recommended that calculated peak flow in public institutions such as State Hydraulics Works (SHW) should made with the help of the WinTR-55 model.